Effects of flux boundary conditions on pore-water pressure distribution in slope - Rahardjo, Harianto (2013)
Many geotechnical analyses commonly ignore the flux boundary conditions at the ground surface to avoid the complexity in determining the actual flux values at the soil-atmosphere interface. However, actual flux boundary conditions can be an important input to many geotechnical analyses, especially those related to unsaturated soils. Therefore, the effects of flux boundary conditions on pore-water pressure distribution in a residual slope are investigated in this paper. The study focuses on infiltration and evaporation processes. The characterization of climatic data in Singapore is presented in this paper to illustrate the quantification of flux boundary conditions. Evaporation rate for the seepage analyses is calculated using Penman's method. The classification of Singapore climate is carried out using Thornthwaite index.